Existence Local and Global of Solution of Initial-Boundary Value Problem for Class of Fractional p-Laplacian Equation with Logarithmic Nonlinearity - Bidi, Younes; Beniani, Abderrahmane (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we study the initial-boundary value problem for class of fractional p-Laplacian equation with logarithmic nonlinearity. By means of the Galerkin approximations, we prove the local and global existence of the weak solutions.We also establish finite time Blow up.